An Enterprising Profession Monkey-trapping - Yellurkar, D. D. (Indian Forester, 1975)
An enterprising professional trapper is employed by the Zilla Parishad, Amravati, to trap black faced monkeys (Langurs). This interesting trapping operation is narrated in detail by the another.